GAMBARAN PERAWATAN TRADISIONAL PADA PERIODE EARLY POST PARTUM DALAM PROSES INVOLUSI DI PRAKTEK MANDIRI BIDAN CLARA KOTA AMBON TAHUN 2018 - Paunno, Magdalena (MOLUCCAS HEALTH JOURNAL, 2021)
Dece Tetimelay, 2018. The descriptive study of traditional treatment on early post partum period in involution process in local Midwifeâ€™s independent practice clara Ambon City â€Post partum (Childbirth/Puerperium) comes from latin it is â€œpuerâ€ and it means baby and â€œparousâ€ that has meaning birth. Post partum period begin after placentaâ€™s birth and this is end when all the tool of uterus back to the first condition before pregnant and this event is continuous about 6 weeks. This research has purpose to know the descriptive study of traditional treatment on early post partum period in involution process in Local Midwifeâ€™s independent practice clara Subdistric Nusaniwe Ambon City 2018. This research used descriptive analysis design that is doing to know the value of each variable or more and its character is independen without made a relation or comparison with other variable. Total sample used in this research is 32 respondens. The result of this research are found traditional traetment practicum on early post partum period that is Bakancing 21,9 percent, forbidden food 87,5 percent, consumption of meal 78,1 percent with respondens characteristic of age about 21-31 years old with 87,5 percent, their grade of education is Senior High School with 84,4 percent, their job is house woman with 65,6 percent, the helper of birthis nurse with 49.4 percent, their paritas is two child with 49,9 percent and one hundred percent respondens have zise of fundus uteri stall in the midlle of simpisis centre. The suggestion in this research is usefull for the nurse that is necesarry to do medical socialiszation related to the tretment on post partum period for all the mother in order to know the information about the right treatment on post partum period so they can not made a mistake on that case.Â Key words : Traditional treatment, Early post partum period.